FISHES DIVERSITY AT THE AREA OF GUNUNG CIREMAI NATIONAL PARK, WEST JAVA - Rachmatika, Ike; Wahyudewantoro, Gema (JURNAL BIOLOGI INDONESIA, 2009)
SHORT COMUNICATIONFishes Diversity at the area of Gunung Ciremai National Park, West Java